Phenomena and Indicators of Success in the Quality of Inclusive Education in Islamic Perspective - Fadilah, Arif; Saputra, Awang; Nurhalim, Nurhalim; Rivaldy, Nurdin (JSSH (Jurnal Sains Sosial dan Humaniora), 2025)
The research aims to explain the problems and phenomena of inclusive education and to find the success indicators of the quality of inclusive education from the perspective of the Qur'an and Hadith. This research uses a qualitative descriptive study of literature published in 2010-2022. The problems are management, infrastructure, financing, collaboration, learning processes, curriculum, educators and education staff, students, parents, and difficulties in assessment and policies. Inclusive education is dominated at the age of 5-9 years, where a total of 149 thousand students are attending inclusive education at the elementary school level. Indicators of the successful based on rational aspects, commitment, cooperation, team solidity, resources, leadership, speed of action and parents. An overview of the Qur'an and Hadith as motivation to build quality inclusive education in the following Qur'an 3:55, 5:2, 6:66, 48-10, 13:12, 3:39, 3:9, 8: 7-8, while the Hadith Bukhari, and Muslim. The research implies that the better the phenomenon of inclusive education is achieved, the closer it is to the indicator of the success of inclusive education in Indonesia. Further research is needed to explore the management of inclusive education in Islamic educational institutions referring to indicators of educational success.